Skills development for improved employee performance in South African municipalities - Sarah Sibiya; Shikha Vyas-Doorgapersad (Insights into Regional Development)
This study explores skills development for improved employee performance in South African municipalities. This study was motivated by the need to expedite local government service delivery, hampered by municipal employees' poor capacity and skills over the years. Many municipalities need help to fulfil their service delivery obligations because of the requisite skills' scarcity, absence, and shortage. The study explores the skills development of municipal employees (focus) in South African municipalities (locus). It does not focus on one chosen municipality but looks at the situation holistically from a broader perspective. The study aims to find answers to the research question: what are the causes of skills shortage on employee performance in South African municipalities? A qualitative desktop study was adopted to find answers to the guiding question, and various secondary documents were analysed to gather information. The human capital theory was used as a framework for the study. The findings show that most local government employees' skills are outside the dictates of the current era. The study recommends interventions, among other things, improving local government skills development funding, adequately implementing monitoring and evaluation practices, developing soft skills for the current fourth industrial revolution era, and performing regular municipal skills audits.